An Observational Study of the Equivalence of Age and Duration of Diabetes to Glycemic Control Relative to the Risk of Complications in the Combined Cohorts of the DCCT/EDIC Study - Bebu, Ionut (Diabetes Care, 2020)
OBJECTIVE: This epidemiological analysis of the pooled Diabetes Control and Complications Trial/Epidemiology of Diabetes Interventions and Complications (DCCT/EDIC) cohort describes the equivalence of a 1-percentage point increase in HbA(1c) (such as from 7% to 8%) and years of additional age or duration of type 1 diabetes (T1D) relative to the risk of complications. RESEARCH DESIGN AND METHODS: Separate Cox proportional hazards models determined the number of additional years of age and/or duration of T1D that would result in the same increase in risk of microvascular (retinopathy, nephropathy, and neuropathy) and cardiovascular complications and mortality as a 1-percentage point increase in HbA(1c). RESULTS: The risk of any cardiovascular disease associated with a 1-percentage point increase in HbA(1c) was equivalent to the risk associated with 4.3 (95% CI 2.7–5.9) additional years of age or 5.6 (95% CI 2.7–6.5) additional years’ duration of T1D. The risk of estimated glomerular filtration rate <60 mL/min/1.73 m(2) and/or end-stage renal disease associated with a 1-percentage point increase in HbA(1c) was equivalent to the risk associated with 12.1 (95% CI 8.3–15.9) additional years of age or 18.0 (95% CI 4.3–31.7) additional years’ duration of T1D. The proliferative diabetic retinopathy risk associated with a 1-percentage point increase in HbA(1c) was equivalent to the risk associated with 6.4 (95% CI 5.3–7.4) additional years’ duration of T1D, while for mortality risk, it was equivalent to the risk associated with 12.9 (95% CI 6.6–19.3) additional years of age. CONCLUSIONS: Our results help evaluate the impact of glycemia on advanced complications in a way that may be more interpretable to health care providers and individuals with T1D.